The use of tranquilizer compounds in fattening rations for steers. - Koch, B.A.; Smith, E.F.; Richardson, D.; McCarter, M.M. (Kansas Agricultural Experiment Station, 2011)
The steers used in this fattening trial were part of a larger group used in a wintering study reported on page 54 of Kansas Circular 358. At the beginning of the fattening period the ration was gradually changed from a high roughage, wintering type, to a high energy, fattening type. Individual calves remained in the same experimental groups as during the wintering trials but the groups were moved from the outdoor lots to concrete lots in which shelter was available.
Keywords: Beef; Tranquilizer; Steers